The current status, attitudes, and practices concerning maternal pertussis vaccination in obstetric delivery facilities in Kanagawa Prefecture, Japan: a questionnaire survey - Kazuya Hiiragi; Soichiro Obata; Etsuko Miyagi; Shigeru Aoki (Human Vaccines & Immunotherapeutics, 2021)
This study investigated the implementation status, attitudes, and practices regarding maternal pertussis vaccination in delivery facilities in Kanagawa, Japan. We conducted a questionnaire survey of pertussis vaccination during pregnancy at 125 delivery service facilities, excluding midwifery clinics, in Kanagawa Prefecture from June 18 to July 20, 2020. The questionnaire comprised multiple-choice items, with single or multiple answers depending on the question. Of the 125 facilities surveyed, valid responses were obtained from 72 facilities (58%). There were 41 primary clinics with birthing facilities (57%), 16 general hospitals (not designated perinatal centers) (22%), 10 regional perinatal centers (14%), and five tertiary perinatal centers (7%). None of the facilities administered pertussis vaccination during pregnancy. Forty facilities (56%) reported knowledge of the severity of neonatal and infant pertussis infections. Twenty-three facilities (32%) reported knowledge of the prevention of pertussis infection by vaccination during pregnancy. All facilities reported willingness to consider vaccination if included in the Japanese guidelines. In Japan, the pertussis vaccination during pregnancy is not highly practiced by obstetricians; thus, it is not as popular as in other countries. Further studies are needed to promote strategies to prevent pertussis infection in the neonatal and infant periods.